Indoor Radon Mapping and Assessment Excess Lifetime Cancer Risk in the Quarry Area of Shira, Bauchi State Nigeria - Baballe, Auwalu; S. A. Dalhatu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The radioactive gas radon (Rn) is considered an indoor air pollutant due to its detrimental effects on human health. In fact, exposure to Rn is among the most important causes of lung cancer after tobacco smoke. The study aims to measure indoor radon concentration and evaluate the excess lifetime cancer risk from its exposure. The indoor radon concentrations were measured using electronic semiconductor detector (RAD7). The indoor radon activity concentration varies from 76.0 Bqm-3 to 217.4 Bqm-3 with a mean value of 149.3 Bqm-3. The result for Annual effective dose (Eaed) calculated from the measured indoor radon was 3.79 mSv/y, which are clearly above the permissible limit of 100 Bqm-3 and 1.15 mSv/y set by (WHO) and (UNSCEAR, 2000). The potential health risk was determined by computing Excess Lifetime Cancer Risk (ELCR) and lung cancer cases per year per million person (LCC). The map for the distribution and exposure rate due to indoor Radon for the study area was also plotted using Golden surfer 12 software. The average values for (ELCR) and (LCC) are respectively, 1.4×10-2 and 70.07 per millions, which is lower than the limit range of 170–230 per million persons recommended by ICRP. These measurements provide valuable insights for evaluating public radiation exposure and establishing robust radiological safety protocols.